1998
DOI: 10.1095/biolreprod59.2.321
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Exposure of Ovine Embryos to an Advanced Uterine Environment Does Not Affect Fetal Weight but Alters Fetal Muscle Development1

Abstract: Embryo transfer techniques may result in fetuses that are heavier at birth and that have been described as highly muscled. The aim of this study was to investigate myogenesis in lambs derived from embryo transfer. Embryos were transferred at Day 3 (estrus = Day 0) to a 3 days-advanced uterine environment, maintained there for 3 days, recovered, and then returned to a synchronous (Day 6) uterus; these fetuses comprised the asynchronous group. Control animals were created by synchronous embryo recovery and singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 17 publications
3
25
1
1
Order By: Relevance
“…However, secondary to primary fiber ratio in ST muscle of fetuses from undernourished ewes tended to be lower compared with fetuses from well-fed ewes. Increase or decrease in secondary to primary fiber ratio as the result of nutritional treatments in the present study is compatible with the reported results in response to nutritional manipulations (Maxfield et al, 1998a and1998b;Crosier et al, 2002;Quigley et al 2005).…”
Section: Figuresupporting
confidence: 93%
See 1 more Smart Citation
“…However, secondary to primary fiber ratio in ST muscle of fetuses from undernourished ewes tended to be lower compared with fetuses from well-fed ewes. Increase or decrease in secondary to primary fiber ratio as the result of nutritional treatments in the present study is compatible with the reported results in response to nutritional manipulations (Maxfield et al, 1998a and1998b;Crosier et al, 2002;Quigley et al 2005).…”
Section: Figuresupporting
confidence: 93%
“…Investigation of time points later in gestation, when myogenesis is completed, may reveal whether myogenesis continues longer in fetuses from undernourished ewes, allowing them to attain normal potential for muscle growth. Nevertheless, the evidence indicates that, even after myogenesis is completed, there are still marked differences in muscle fiber characteristics because of nutritional manipulations in sheep suggesting that the early embryonic period may irreversibly program myogenic potential (Maxfield et al, 1998b;Quigley et al, 2005).…”
Section: Figurementioning
confidence: 99%
“…However, such an approach appears to be more relevant keeping in mind the recently pronounced concept [1][2][3]45] that several diseases encountered during adult life might have their origin during the period of foetal development. The same might be true for physical performance and (re)production in domestic species [37,39,40,48]. In this respect one seems to have forgotten that, within the context of research on growth and production of farm animals, Grahm Everitt already warned in 1968 that "The extent to which events of later life may be modified by factors operating during the formative stages appears insufficiently appreciated"(see Bell [4]).…”
Section: Introductionmentioning
confidence: 99%
“…Another example of the sensitivity of foetal development to the environment of the early embryo is the observation by Maxfield et al (1998) that a temporary 3-day exposure of day 3 sheep embryos to an advanced (day 6) uterine environment increased muscle fibre number and the ratio of secondary to primary fibres in the foetus; it also altered the temporal expression of the myogenic gene, myf 5, implying that this gene is involved in prolongation of foetal myoblast hyperplasia.…”
Section: The Embryomentioning
confidence: 99%